The interferon type I signature is present in systemic sclerosis before overt fibrosis and might contribute to its pathogenesis through high BAFF gene expression and high collagen synthesis. Issue 8 (14th September 2015) - Brkic, Zana; van Bon, Lenny; Cossu, Marta; van Helden-Meeuwsen, Cornelia G; Vonk, Madelon C; Knaapen, Hanneke; van den Berg, Wim; Dalm, Virgil A; Van Daele, Paul L; Severino, Adriana; Maria, Naomi I; Guillen, Samara; et al.
Abstract : Background: Interferon (IFN) signature has been reported in definite systemic sclerosis (SSc) but it has not been characterised in early SSc (EaSSc). We aim at characterising IFN type I signature in SSc before overt skin fibrosis develops. Methods: The expression of 11 IFN type I inducible genes was tested in whole-blood samples from 30 healthy controls (HCs), 12 subjects with primary Raynaud's phenomenon (RP), 19 patients with EaSSc, 7 patients with definite SSc without cutaneous fibrosis, 21 limited cutaneous SSc and 10 diffuse cutaneous SSc subjects. The correlation between IFN activity in monocytes, B cell activating factor (BAFF) mRNA expression and type III procollagen N-terminal propeptide (PIIINP) serum levels was tested. Results: In all the SSc groups, higher IFN scores were observed compared with HC. An IFN score ≥7.09 discriminated HCs from patients with SSc (sensitivity=0.7, specificity=0.88, area under receiving operating characteristic (AUROC)=0.82); the prevalence of an elevated IFN score was: HC=3.3%; RP=33.3%, EaSSc=78.9%, definite SSc=100%, limited cutaneous SSc=42.9%, diffuse cutaneous SSc=70.0%. In monocytes an IFN score ≥4.12 distinguished HCs from patients with fibrotic SSc (sensitivity=0.62, specificity=0.85, AUROC=0.76). Compared with IFN-negative subjects, IFN-positive subjects had higher monocyte BAFF mRNA levels (19.7±5.2 vs 15.20±4.0, p=2.1×10 −5 ) and serum PIIINP levels (median=6.0 (IQR 5.4–8.9) vs median=3.9 (IQR 3.3–4.7), p=0.0004). Conclusions: An IFN type I signature is observed in patients with SSc from the earliest phases of the disease, even before overt skin fibrosis. The presence of IFN type I signature in monocytes is correlated with BAFF mRNA expression and serum PIIINP levels, supporting a contribution in the pathogenesis and progression of SSc.